Hydrodynamics, Mass and Heat Transfer in Reactive Distillation - Radhaa, Majid S.; Sukkar, Khalid A.; Ali, Jamal M.; Shakoor, Zaidoon M.; Manwel, Niran (Al-Khwarizmi Engineering Journal, 2008)
The ethyl acetate synthesis via heterogeneous reactive distillation is studied experimentally using ethanol and acetic acid. Three types of cation exchanging resins were used as catalysts: Zerolit 225, Zerolit 226 and Ambylite 400. Experiments were carried out in two units of the same dimensions. Each unit consisted of three sections: rectifying, reactive and stripping sections of heights (60+25+20) cm respectively and 2.5cm column diameter. The first unit (column-A-) was a fractionation type and the second unit (column-B-) was packed column. The packing type was hollow glass cylinders with 10 mm height, and 4, 5 mm inner and outer diameter respectively. The experiments were carried out by using two operation modes. The semi-batch and continuous operation mode. In the first part of present investigation, the semi-batch mode was used to evaluate the catalyst type and to evaluate the performance of reactive distillation unit configuration (Fractionation and packed column). Results show that, the column-B- gave higher conversion rates than column-A-. This is attributed to the high surface area available for liquid vapour contact in packed type column, which leads to increasing mass transfer rates. On the other hand, Ambylite 400 catalyst showed higher activity for esterification reaction than other two types of catalysts. The second part of work continued with column -B- only. It is well known that, the esterification process is regarded one of exothermic reactions. Therefore, the monitoring of the temperature distribution along column axial for all three types of catalysts showed that the temperature distribution was essentially the same due to steady state operation in continuous operation mode. On the other hand, the effect of reflux ratio on temperature distribution was clearly noted, that is as the reflux ratio increased the temperature distribution along the column was reduced for each type of catalysts. On the other hand, the experimental results point that, as a reflux ratio increases the conversion rates of acetic acid is increased too because such increasing is related to high mass transfer rates between vapour and liquid along reactive distillation column.